2-Methyl-3-nitrobenzonitrile - Han, Guo-zhi (International Union of Crystallography, 2008)
The asymmetric unit of the title compound, C(8)H(6)N(2)O(2), contains two independent molecules, the aromatic rings of which are oriented at a dihedral angle of 1.68 (3)°. Intramolecular C—H⋯O hydrogen bonds result in the formation of two non-planar six-membered rings, which adopt envelope and twisted conformations. In the crystal structure, intermolecular C—H⋯O hydrogen bonds link the molecules. There are π–π contacts between the benzene rings [centroid–centroid distances = 3.752 (3) and 3.874 (3) Å].